From the Forefront to the Sidelines: Youth in Post-Revolution Egypt - Omar, Khadiga (AUC Knowledge Fountain, 2014)
This thesis examines the reasons for the declining role of youth as effective political players since the Egyptian Revolution in 2011. Particularly looking at the “Revolutionary Youth”, this study investigates why their activism over the course of the past four years could not translate into political power that would lead to the realization of the goals of the revolution. Resource Mobilization Theory, Political Opportunity Structure and Framing constitute a tri-lens through which the political experience of the youth is analyzed in this research. This thesis argues that a) the youth’s organizational dilemma; b) their reliance on protest as the exclusive tool to practice politics; c) and their failure to develop a culturally resonant discourse that attends to people’s socio-economic needs are the reasons for their marginal role in the post-revolution period. Relying on interviews with youth activists as well as a thorough survey of youth movements online pages, this research provides fresh insights explaining the youth experience and presents a point of departure for further research. By understanding social movements as expressions of youth political engagement, the study also aims to highlight the characteristics and implications the “youthful” nature of the revolution has on the ongoing struggle.